Likelihood of injury due to vasovagal syncope: a systematic review and meta-analysis. Issue 7 (8th March 2021) - Jorge, Juliana G; Raj, Satish R; Teixeira, Pedro S; Teixeira, Jose A.C; Sheldon, Robert S
Abstract: Aims: Vasovagal syncope (VVS) is the most common type of syncope and is usually considered a benign disorder. The potential for injury is worrisome but the likelihood is unknown. We aimed to determine the proportion of patients injured due to VVS. Methods and results: A systematic search of studies published until August 2020 was performed in multiple medical and nursing databases. Included studies had data on the proportion of patients with injury due to VVS prior to study enrolment. Random effects methods were used. Twenty-three studies having 3593 patients met inclusion criteria. Patients were diagnosed clinically with VVS, and 82% had >2 syncopal episodes before enrolment. Tilt test was positive in 60% and 14 studies reported comorbidities (32.6% hypertensive). The weighted mean injury rate was 33.5% [95% confidence interval (CI): 27.3–40.5%]. The likelihood of injury correlated with population age ( r = 0.4, P = 0.05), but not with sex, positive tilt test, or hypertension. The injury rates were 25.7% (95% CI: 19.1–32.8%) in studies with younger patients (mean age ≤50 years, n = 1803) and 43.4% (95% CI: 34.9–52.3%) in studies with older patients ( P = 0.002). Nine studies reported major injuries; with a weighted mean rate of major injuries of 13.9% (95% CI: 9.5–19.8%). Conclusion : Injuries due to syncope are frequent, occurring in 33% of patients with VVS. The risk of major injuries is substantial. Older patients are at higher risk. Clinicians should be aware of the risk of injuries when providing care and advice to patients with VVS.